(untitled) (Materiali di Estetica. Terza serie, 2024)
Fear and music have a very fruitful relationship, but they experience a different perspective over time: if fear is instantaneous, the flow of music needs breadth. Fear saves us from danger and then goes out, while music investigates emotions so that they are repeated and are a reason for attraction and return. However, in a piece of music it is easy to express well nuances that have a flavor close to fear: disorientation, restlessness, foreboding. In every era, musical literature has tried to express these colours, finding in more recent times a strong connection with psychoanalysis, film language and new technologies.